PZT Actuated MEMS Membrane Characterization and Post Simulation for Digital Loudspeaker Array Application. (2016) - Casset, F.; Laroche, B.; Bouchet, S.; Desloges, B.; Leclere, Q.; Morisson, R.; Bohard, Y.; Goglio, J.P.; Fanget, S.
Abstract: A Digital Loudspeaker Array (DLA) is an electro-mechanical transductor which receives a numerical signal as input data and allows the analogical conversion directly in the air. We designed PZT actuated membranes in order to obtain the highest acoustic pressure as possible. We built 256-MEMS-membranes DLAs using a generic PZT technology and digital acoustic reconstructions of the sound have been already demonstrated using our MEMS-DLA. In this paper, using FEM simulations, we evidence that residual stresses are responsible of the high distortion level measured on our demonstrators. A stress compensated technology was established using FEM approach. Acoustic characterization of stress compensated demonstrators proves distortion decreased and validates our hypothesis.